Investigating weather information needs of smallholder farmers in the Eastern Cape province of South Africa - Mantshiyose, Abenathi (Department of Environmental and Geographical Science, 2023)
South Africa is continuously experiencing irregular weather and climate, which is attributed to climate change and the El Niño Southern Oscillation. These have resulted in temperature increases, irregular rainfall patterns, and increased frequency of extreme events. In South Africa, smallholder farmers are the most vulnerable to extreme weather events due to their limited capacity to adapt. Their vulnerability results from a series of factors constraining their ability to adapt, such as limited resources, knowledge, and skills. Furthermore, smallholder farmers are highly dependent on rainfed agriculture, making them more sensitive. The lack of weather information that is tailored for user needs or adapted well enough is also a concerning issue that exacerbates the living conditions of smallholder farmers. This makes it difficult for them to sustain their agricultural activities. Over the years, weather information has been recognized as having the potential to be useful in agriculture, especially in informing farming practices, planning, and reducing weather events impacts among smallholder farmers. However, access and use of weather information that applies to the context of smallholder farmers which is tailored to meet smallholder farmers needs, has been limited and has contributed to limited understanding and low use levels of weather information. This has increased the need to understand the weather information needs of smallholder farmers as this is important to ensure that farmers can effectively use and understand the information. In South Africa, limited studies have looked at the weather information needs of smallholder farmers. Hence, a shift of attention towards investigating the weather information needs of smallholder farmers has increasingly become necessary. The present study investigated how to better communicate the weather information needs of smallholder farmers in the Eastern Cape province of South Africa. A mixed-methods approach was used to collect and analyze the data. Interviews with open-ended and closed-ended questions were conducted with smallholder farmers and agricultural extension officers. Interviews were conducted to gain an insight on the baseline and characteristics of weather information farmers receive and their needs. The same was done with extension officers to get their insight on the needs of farmers and the needs of extension officers. 2 The findings of the study confirm that the current weather information system is inefficient as the information does not fully meet the needs of smallholder farmers. Most of the farmers expressed that they currently receive information on rainfall, temperature, and heavy rainfall but stated that they would like to receive information on drought as they are currently experiencing dry periods. The farmers mentioned that they receive weather information mostly from the television, radio, and a few from weather apps. Most of the farmers receive weather information in maps and audio, expressing that maps make it easy for them to visualize and understand the information. From the television, they receive the information in IsiXhosa and IsiZulu, and they mentioned that weather information in IsiXhosa is easy to understand as it is their local language. In weather apps, farmers mentioned that they receive weather information in English and expressed concerns about understanding weather information in English. As a result, most farmers preferred receiving weather information in IsiXhosa as they can understand the language. Additionally, farmers also expressed that they only receive weather information daily, and they stated that they would like to receive weather information daily, weekly, monthly, and seasonally to plan their farming activities and to know when to plant. Furthermore, most of the farmers expressed that they encounter some challenges with the information they receive. Some of the challenges included issues such as the inaccuracy of the information and scale issues. The farmers complained that the information they receive is not downscaled to their local scale, making it difficult for them to apply the information on their local scale decisions. Therefore, without significant improvement of the issues mentioned above and addressing the weather information needs of farmers, weather information use and understanding will remain low and will increase the vulnerability of smallholder farmers to extreme weather events. To prevent this, there is a growing need for weather information to meet the needs of smallholder farmers so that they can understand and use the information efficiently, especially in the face of increasing extreme weather events such as drought in South Africa.